The impact of cigar pack size and pricing policies on youth and adult cigar use in the US - Jensen, Jessica King; Ko, Hyunkyu; Kim, Jaewhan; Delnevo, Cristine D.; Azagba, Sunday (Drug and alcohol dependence, 2023)
Over 250 US localities have adopted cigar pack quantity and price policies. No empirical studies exist on their impact on tobacco use. A quasi-experimental design was used to assess the impact of cigar policies on cigar and cigarette use among (1) Minnesota youth (n=569,528, triennially 2007–2019); (2) New York youth (n=111,236, annually 2000–2020), (3) New York adults (n=62,295, annually 2003–2019), and (4) District of Columbia (DC) adults (n=5027, annually 2015–2019). We estimated the county-level policy coverage for 15 local policies in Minnesota. Differences-in-differences approach was used to compare the policy in NYC with the rest of the state (no policy). We examined changes in DC use before and after policy implementation. Analyses adjust for sociodemographic characteristics. In Minnesota, youth in counties with a greater proportion of the population covered by a policy had lower odds of cigar use (AOR: 0.51; 95% CI: 0.38–0.69). Similarly, adult cigar use in DC declined following policy enactment (AOR: 0.65; 95% CI: 0.46–0.93). Cigarette use also decreased in both Minnesota and DC following policy enactment. However, in New York, the NYC policy did not have a significant impact on cigar use among youth (AOR: 0.95; 95% CI: 0.47–1.93) or adults (AOR: 1.98; 95% CI: 0.85–1.37) in NYC compared to the rest of the state. The only significant effect in NYC was reduced odds for adult cigarette use (AOR: 0.79; 95% CI: 0.68–0.92). Findings suggest regulating cigar packaging could decrease cigar consumption without increasing cigarette consumption, but effects may differ across jurisdictions. •This study provides the first assessment of cigar pack policy impact on cigar use.•Policies were associated with decreases in use among Minnesota youth and DC adults.•Minimum cigar pack sizes and prices appear to be promising approaches to reduce use.